2021
DOI: 10.1038/s41467-021-25238-7
|View full text |Cite
|
Sign up to set email alerts
|

Excessive ammonium assimilation by plastidic glutamine synthetase causes ammonium toxicity in Arabidopsis thaliana

Abstract: Plants use nitrate, ammonium, and organic nitrogen in the soil as nitrogen sources. Since the elevated CO2 environment predicted for the near future will reduce nitrate utilization by C3 species, ammonium is attracting great interest. However, abundant ammonium nutrition impairs growth, i.e., ammonium toxicity, the primary cause of which remains to be determined. Here, we show that ammonium assimilation by GLUTAMINE SYNTHETASE 2 (GLN2) localized in the plastid rather than ammonium accumulation is a primary cau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 45 publications
3
115
0
Order By: Relevance
“…We noticed varying degrees of increases in the root GS and NADH-GDH activities when the NH 4 + concentration increased from 0% to 50%. Elevated activities of GS and NADH-GDH were required in the assimilations of the excessive NH 4 + to prevent toxicity, consistent with the results regarding certain studies in vegetables [41,45], crops [15,46], and Arabidopsis [11,47]. As the NH 4 + concentration increased from 50% to 100%, the greatest reinforcements of both the root GS and NADH-GDH activities were monitored in the NH 4 + -tolerant species ageratum, followed by the moderately NH 4 + -sensitive species petunia, but in the extremely NH 4 + -sensitive salvia, root GS and NADH-GDH activities were not significantly affected and in some cases even reduced, in response to high NH 4…”
Section: Explorations Of the Nhsupporting
confidence: 89%
See 1 more Smart Citation
“…We noticed varying degrees of increases in the root GS and NADH-GDH activities when the NH 4 + concentration increased from 0% to 50%. Elevated activities of GS and NADH-GDH were required in the assimilations of the excessive NH 4 + to prevent toxicity, consistent with the results regarding certain studies in vegetables [41,45], crops [15,46], and Arabidopsis [11,47]. As the NH 4 + concentration increased from 50% to 100%, the greatest reinforcements of both the root GS and NADH-GDH activities were monitored in the NH 4 + -tolerant species ageratum, followed by the moderately NH 4 + -sensitive species petunia, but in the extremely NH 4 + -sensitive salvia, root GS and NADH-GDH activities were not significantly affected and in some cases even reduced, in response to high NH 4…”
Section: Explorations Of the Nhsupporting
confidence: 89%
“…These ammonium toxicity symptoms have evoked numerous hypotheses on the cause: depletion of carbon supply [8,9], energy overconsumption for futile ammonium cycling [8,10], and a recently elucidated mechanism of acidic stresses produced by disordered pH regulation [11]. Nonetheless, the information linked with the N assimilation pathways to explain the ammonium tolerances, especially in bedding plants, remains scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect should be taken into account in the case of overexpression of NH 4 + transporter genes, when plants do not have enough time to assimilate the absorbed NH 4 + , as has already been noted by some researchers [ 71 , 73 ]. The exact mechanism of plant growth disorders due to NH 4 + toxicity is still unknown, although several hypotheses have been put forward, including futile transmembrane NH 4 + cycling, deficiencies in inorganic cations and organic acids, impaired hormonal homeostasis, disordered pH regulation and the uncoupling of photophosphorylation [ 210 ]. High concentration of NH 4 + is also one of the causes of plant death due to the use of broad-spectrum herbicides based on phosphinotricin (PPT).…”
Section: Ammonium Toxicity and Resistance To Phosphinothricinmentioning
confidence: 99%
“…On the other hand, the multiple hypotheses regarding the NH 4 + toxicity [ 209 , 222 ] were recently joined by another one. According to Hachiya et al [ 210 ], the primary cause of NH 4 + toxicity is not its high concentration, but rather acidic stress resulting from assimilation of these high amounts by the plastid form of GS. Whatever the exact mechanisms of NH 4 + toxicity or of the PPT effect, the increase in plant PPT resistance achieved through overexpression of GS or other N metabolism genes is absolutely insufficient for the commercial use of such plants.…”
Section: Ammonium Toxicity and Resistance To Phosphinothricinmentioning
confidence: 99%
“…The differences between GS isoforms are increasingly being studied. The main cause of ammonium toxicity in Arabidopsis was found to be ammonium assimilation of GS2 rather than ammonium accumulation [15]. Isotopic-tracing experiments and genetic evidence indicated that three of the five GS1s work together to remobilize nitrogen and fill seeds in Arabidopsis [16].…”
Section: Introductionmentioning
confidence: 99%